Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s12070-012-0615-5
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity of Different Concentrations Povidone-Iodine Solution Applied to the Middle Ear Cavity of Rats

Abstract: To investigate the ototoxic effects of different concentrations of povidone-iodine solutions applied to the middle ear cavity of rats using distortion product otoacoustic emissions. 24 healthy 3-3.5-month-old adult female Sprague-Dawley rats were randomly divided into three groups. The group A (n = 8 ears) received 5 % povidone-iodine solution to the right ear, the group B (n = 8 ears) received 7.5 % povidone-iodine solution to the right ear and the group C (n = 8 ears) received 10 % povidone-iodine solution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
(24 reference statements)
1
18
0
Order By: Relevance
“… c) Cochlear damage with exposure time of 60 min with Iodophor in 70% alcohol. d) Vestibular damage seen with Iodophor in 70% with exposure times of 30-60min T Morizono, 1982 [ 7 ] 30 Chinchilla Solutions tested: a) Povidone-iodine Solution at 1:10 dilution (1.0% available iodine) b) Povidone-iodine Scrub* at 1:10 dilution (0.75% available iodine) c) Povidone-iodine Scrub at 1:100 dilution Exposure time 10mins Effect on Compound Action potential (CAP) tested 2 hours, 24 hours post exposure *Scrub contains detergent Contralateral ear to experimental ear a) Povidone-iodine Scrub more toxic to cochlear function then solution b) Evoked action potential measure at round window, no change 2 hours after exposure with 1:10 dilution of Iodine Solution c) Evoked action potential measure at round window 2 hours after exposure with 1:10 dilution of Iodine Scrub caused severe depression at all tested frequencies (2, 4, 8, 12kHz) d) Increased toxicity with increased concentrations for both solution and scrub T Morizono, 1983 [ 8 ] 30 Chinchilla Solutions at different dilutions d) Povidone-iodine Solution at 1:10 dilution (1.0% available iodine) e) Povidone-iodine Scrub* at 1:10 dilution (0.75% available iodine) f) Povidone-iodine Scrub at 1:100 dilution Duration of exposure time 10mins Effect on Compound Action potential (CAP) tested 2 hours, 24 hours post exposure *Scrub contains detergent Contralateral ear to experimental ear a) High frequency losses (8 and 12kHz) after 10, 30 and 120min exposure to iodine scrub at 1:100 dilution T. Inchibangase, 2011 [ 6 ] 70 Guinea Pigs – Divided into groups based on age (infant, young and adult) Solution tested a) Povidone-iodine 10% solution b) Povidone-iodine scrub Effect on Compound Action potential (CAP) tested at 24h, 7days and 28days Contralateral ear to experimental ear a) No action potential at 24hours after application of Povidoneiodine scrub b) 24 hours after exposure to povidone-iodine solution, significant ototoxicity measured in infant group, less in young and least in adult c) 8 fold dilution of povidoneiodine solution showed no hearing loss in adults, loss for young at 2 and 4kHz d) Showed aged related variation associated with ototoxicity in guinea pigs M. Ozkiris [ 16 ] 24 Sprague-Dawley Rats Solution tested a) 5, 7.5, 10% Povidone-iodine solutions No exposure time given. Otoacoustic emissions measured at 1 and 10 days after exposure Contralateral ear to experimental ear a) At 5% concentration some statistically significant decreased hearing at day 1 but resolved by day 10 b) At 7.5% and 10%, day 10 results showed decreased in hearing in frequencies ranging from 1.5-12kHz ...…”
Section: Methodsmentioning
confidence: 99%
“… c) Cochlear damage with exposure time of 60 min with Iodophor in 70% alcohol. d) Vestibular damage seen with Iodophor in 70% with exposure times of 30-60min T Morizono, 1982 [ 7 ] 30 Chinchilla Solutions tested: a) Povidone-iodine Solution at 1:10 dilution (1.0% available iodine) b) Povidone-iodine Scrub* at 1:10 dilution (0.75% available iodine) c) Povidone-iodine Scrub at 1:100 dilution Exposure time 10mins Effect on Compound Action potential (CAP) tested 2 hours, 24 hours post exposure *Scrub contains detergent Contralateral ear to experimental ear a) Povidone-iodine Scrub more toxic to cochlear function then solution b) Evoked action potential measure at round window, no change 2 hours after exposure with 1:10 dilution of Iodine Solution c) Evoked action potential measure at round window 2 hours after exposure with 1:10 dilution of Iodine Scrub caused severe depression at all tested frequencies (2, 4, 8, 12kHz) d) Increased toxicity with increased concentrations for both solution and scrub T Morizono, 1983 [ 8 ] 30 Chinchilla Solutions at different dilutions d) Povidone-iodine Solution at 1:10 dilution (1.0% available iodine) e) Povidone-iodine Scrub* at 1:10 dilution (0.75% available iodine) f) Povidone-iodine Scrub at 1:100 dilution Duration of exposure time 10mins Effect on Compound Action potential (CAP) tested 2 hours, 24 hours post exposure *Scrub contains detergent Contralateral ear to experimental ear a) High frequency losses (8 and 12kHz) after 10, 30 and 120min exposure to iodine scrub at 1:100 dilution T. Inchibangase, 2011 [ 6 ] 70 Guinea Pigs – Divided into groups based on age (infant, young and adult) Solution tested a) Povidone-iodine 10% solution b) Povidone-iodine scrub Effect on Compound Action potential (CAP) tested at 24h, 7days and 28days Contralateral ear to experimental ear a) No action potential at 24hours after application of Povidoneiodine scrub b) 24 hours after exposure to povidone-iodine solution, significant ototoxicity measured in infant group, less in young and least in adult c) 8 fold dilution of povidoneiodine solution showed no hearing loss in adults, loss for young at 2 and 4kHz d) Showed aged related variation associated with ototoxicity in guinea pigs M. Ozkiris [ 16 ] 24 Sprague-Dawley Rats Solution tested a) 5, 7.5, 10% Povidone-iodine solutions No exposure time given. Otoacoustic emissions measured at 1 and 10 days after exposure Contralateral ear to experimental ear a) At 5% concentration some statistically significant decreased hearing at day 1 but resolved by day 10 b) At 7.5% and 10%, day 10 results showed decreased in hearing in frequencies ranging from 1.5-12kHz ...…”
Section: Methodsmentioning
confidence: 99%
“…This can explain why 5% povidone-iodine does not have a toxic effect on cochlea in COM in the present study. Among the literature reviewing the short-and long-term effects of iodine solution related ototoxicity, Ozkiris mentioned that 5% povidone-iodine solution led to significant short-term hearing loss on the first day that resolved by day 10 while, at 7.5% and 10%, there was a decrease in hearing that persisted for at least 10 days in rats 13 . Yagiz detected no effects following 10% povidone-iodine exposure at 10 days and 4 weeks in guinea pigs 14 .…”
Section: Discussionmentioning
confidence: 99%
“…All evidence of povidone-iodine-related ototoxicity has come from a small number of animal studies. Most of these studies found damage in the cochlea using histologic sectioning or electrophysiological tests ( Perez et al, 2000 ; Ichibangase et al, 2011 ; Ozkiris et al, 2013 ). Cochlea damage was found histologically in guinea pigs after 30 min of exposure to povidone-iodine alcoholic solution, but vestibular damage required longer exposure times ( Aursnes, 1982 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown ototoxicity after the application of povidone-iodine to the middle ear of rats ( Yagiz et al, 2003 ; Ichibangase et al, 2011 ; Ozkiris et al, 2013 ). The concentration of the povidone-iodine solution used might account for the severity of the hearing loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation